1985
DOI: 10.1557/proc-50-273
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Basaltic Glass in Seawater : Experiments and Thermodynamic Modelling

Abstract: The reaction of basalt glasses with natural waters were proposed as analog systems to the long-term alteration of nuclear waste glasses in the geosphere [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…After one day to a few months of alteration, the crystals were covered by an amorphous silica-rich deposit whose chemical composition and structure changed into saponite. Similar results have been obtained by Thomassin and Touray (1982) and Crovisier et al (1982Crovisier et al ( , 1983Crovisier et al ( , 1985 for basaltic glass altered in seawater. Crovisier et al (1982) have observed the crystallization of hydrotalcite after 20 days of alteration of the basaltic glass in seawater at 50~ They also showed that the crystals were covered by a silico-alumino-magnesian gel whose composition evolves to a saponite (480 days) 9 The association of hydrotalcite with saponite has also been observed by Schmitz et al (1982) in marine sediments from the Galapagos rifts, and by Larsen et al (1991) for basaltic glass altered experimentally in deionized water.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…After one day to a few months of alteration, the crystals were covered by an amorphous silica-rich deposit whose chemical composition and structure changed into saponite. Similar results have been obtained by Thomassin and Touray (1982) and Crovisier et al (1982Crovisier et al ( , 1983Crovisier et al ( , 1985 for basaltic glass altered in seawater. Crovisier et al (1982) have observed the crystallization of hydrotalcite after 20 days of alteration of the basaltic glass in seawater at 50~ They also showed that the crystals were covered by a silico-alumino-magnesian gel whose composition evolves to a saponite (480 days) 9 The association of hydrotalcite with saponite has also been observed by Schmitz et al (1982) in marine sediments from the Galapagos rifts, and by Larsen et al (1991) for basaltic glass altered experimentally in deionized water.…”
Section: Discussionsupporting
confidence: 90%
“…Thermodynamic modelling made by Crovisier et at (1985) using the computer code DISSOL (Fritz 1975(Fritz , 1981 showed that hydrotalcite is not stable for longterm in seawater. The replacement of this mineral by saponite during basaltic glass alteration was predicted by the geochemical code DISSOL as the result of magnesium decrease and silica increase in solution.…”
Section: Discussionmentioning
confidence: 99%
“…13.0 (Crovisier et al, 1985), line 2 = tektites (Barkatt et al, 1984), line 3 = basaltic glass (Gislason and Eugster, 1987), line 4 = quartz (Rimstidt and Barnes, 1980). Data points (shown by X) = rhyolitic glasses (White and Claassen, 1980 Steen-Mclntyre (1975) advocated the use of the hydration rate of pumice as a means of dating ash beds.…”
Section: Bmentioning
confidence: 99%
“…Ewing and Haaker, 1979;Byers et al, 1985;Lutze et al, 1985). To model the long-term behaviour and stability of this radioactive waste confinement host studies have concentrated on laboratory corroded basaltic and synthetic borosilicate glasses and naturally altered basaltic glasses (Furnes, 1975(Furnes, , 1978Seyfried Jr. and Bischoff, 1979;Allen, 1982;Malow et al, 1984;Crovisier et al, 1983Crovisier et al, , 1985Crovisier et al, , 1987Crovisier et al, , 1989aCrovisier et al, , 1989bGrambow, 1985;Grambow et al, 1985;Berger et al, 1987Berger et al, , 1988Berger et al, , 1994Gislason and Eugster, 1987a;Eggleton et al, 1987;Guy and Schott, 1989;Murukami et al, 1989;Jercinovic et al, 1990aJercinovic et al, , 1990bAdvocat et al, 1990Advocat et al, , 1991Advocat et al, , 1998Nesbitt and Wilson, 1992;Ghiara et al, 1993;Gislason et al, 1993;Morgenstein and Shettel, 1994;Daux et al, 1994Daux et al, , 1997Leturcq et al, 1999;Abraitis et al, 2000;Techer et al, 2001). Most of the natural glass dissolution studies were performed in either high ionic strength/seawater solutions or at high temperatures, and many were carried out in closed system batch reactors.…”
Section: Introductionmentioning
confidence: 99%